Forår i studiet af arabiske medier - Skovgaard-Petersen, Jakob (Politik, 2012)
Although dating back to the late 19th century, research in Arab media has been weak and marginal until the 1990s. Around that time, the deregulation and privatization of media, and the rise of pan-Arab satellite TV, had led to a dramatic increase in the quality and impact of the Arab media, locally, regionally and gradually even globally. Scholarship has taken up a number of themes – big and small media; local and regional public; Saudization; translocal Islamic identity; TV-dramas as social comment, blogs – that were clearly visible in this new, invigorated media environment. Along with these themes, there has been an ongoing discussion about the democratic potential of the new, competitive media, and the events of 2011 will be seen as a con rma- tion of their political impact. is again raises questions as to the changes in Arab media that the political transformations will bring about.